2020
DOI: 10.33546/bnj.1119
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Competency Development of Nurses as Perceived by Stakeholders in Vietnam

Abstract: Background: Competency of nurses is vital to safe nursing practice as well as essential component to drive quality of nursing services. Competency development is a continuous process of improving knowledge, attitudes and skills, and is influenced by a numerous of factors.Purposes: This study aims to explore factors that influence the development of competencies of nurses working in clinical settings in Vietnam.Methods: A descriptive qualitative research was conducted in Ho Chi Minh City, Vietnam with a purposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This is in accordance with earlier research stating that the needed competencies and their development need to be thoroughly integrated into the curriculum so that a holistic picture of competency development can be provided and continuity can be ensured [ 28 , 42 ]. Another study showed that it seemed difficult for nurses to apply in practice what they have learned in nursing schools [ 43 ]. They also stated that the inappropriate curricula, focusing on technical competencies, might further complicate continuous competency development which is in alignment with our findings [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with earlier research stating that the needed competencies and their development need to be thoroughly integrated into the curriculum so that a holistic picture of competency development can be provided and continuity can be ensured [ 28 , 42 ]. Another study showed that it seemed difficult for nurses to apply in practice what they have learned in nursing schools [ 43 ]. They also stated that the inappropriate curricula, focusing on technical competencies, might further complicate continuous competency development which is in alignment with our findings [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Professional development was one of the main phases in the nursing career ladder. 11 Other studies stated that continuing professional development could improve competency, increase knowledge, and develop professionalism in providing nursing care. Continuing professional development was one way to improve the competence of nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Higher competency and satisfaction with the quality of care are associated with more positive perceptions of the work environment, ethics, greater empowerment, and occupational commitment. 11 Most nurses in Indonesia only have a diploma education, so Indonesia has much homework to improve and maintain the competence of nurses. The need for a highly educated nursing workforce is evident in the positive patient perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding organizational commitment, Labrague et al (2018) found that organizational commitment is affected by a nurses' age, gender, education, rank, and work experience. Organizational commitment is vital to every nurse because it helps them better care for patients (Naghneh et al, 2017;Ha & Nuntaboot, 2020). On the other hand, the clarity of calling as a nurse makes a nurse have a stronger career and organizational commitment and tend to be willing to help colleagues and strive for the good of the organization (Afsar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%